1960
DOI: 10.1029/jz065i003p00825
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of X-band radiation backscattered from the sea surface

Abstract: A coherent radar was used to measure the ‘sea clutter’ or backscattering of X‐band electromagnetic energy from the sea surface. More than 200 recorded samples of clutter were analyzed to give power spectra of the clutter. Each spectrum was displayed as a function of frequency and of position on the water surface and was also averaged to give the mean spectrum of patches 3750 feet long. Five of the samples showed an anomalous downwind displacement of the clutter by as much as 7 knots. The displays indicate agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1967
1967
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…L. Hicks et ut [34]. empirically established the proportionality of the spectrum width to H/T, while in our paper it follows from the theory; numerical comparison with the experimental data shows that in order to adequately explain the total spectrum width, it is necessary to take into account the fluctuations of wind-drift velocity.…”
mentioning
confidence: 85%
“…L. Hicks et ut [34]. empirically established the proportionality of the spectrum width to H/T, while in our paper it follows from the theory; numerical comparison with the experimental data shows that in order to adequately explain the total spectrum width, it is necessary to take into account the fluctuations of wind-drift velocity.…”
mentioning
confidence: 85%
“…The mean Doppler frequencies for horizontal polarization were greater than those for vertical polarization for the same sea conditions. Pidgeon's measurements for horizontal polarization strengthened the explanation for seaecho, that Hicks et al (1960) used in their paper. However, the sea-echo for vertical polarization, must then be due to a different mechanism.…”
Section: Introductionmentioning
confidence: 67%
“…From the measured Doppler specrra, he concluded that the return could be explained in terms of trains of waves and not by a continuous wave (thus he found the sea is not homogeneous). Hicks et al (1960) obtained with an X-band radar, horizontally polarized, that sea-echoes seemed to come from two sets of scatterers: a set of sea waves of unbroken water, of a period of one-half the wavelength of the radar frequency (slightly rough surface scattering), that produced a strong and symmetrical Doppler spectrum with a mean Doppler frequency equivalent to the particle motion of larger sea waves and a second set of scatterers, of wind driven irregularities, composed of broken water (white caps) which contributed an asymmetrical Doppler spectrum which was only half as strong in amplitude as that from the previous set.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the latter, Hicks et al [17] has shown experimentally that the Doppler spread at high grazing angles is proportional to the wave height divided by the wave period. This relationship has been verified with the Ingara data in a previous publication, [18].…”
Section: B Temporal Correlationmentioning
confidence: 98%